DESIGNING READING MATERIALS BASED ON MAIMOON PALACE - Laoly, Olivia Angelene; Alrajafi, Gali; Tarigan, Natalia Widya Pasca (ELT (English Language Teaching Prima Journal), 2024)
Reading is a crucial language skill that students must master to enhance their understanding and knowledge of various subjects. In terms of reading, various topics of text are very necessary for the language learners to make them becoming more knowledgeable. It is crucial to design reading materials which is attractive and interesting to attract students to read. This research aims to know exactly the story behind the Maimoon palace and to transcribe the story to the form of reading text. In order to conduct this research, interview method was used by the researchers to collect data. After conducting the research, there were several findings about the story of Maimoon palace from the source person in the Maimoon palace. Then, the result of interview was written in the form of story of the palace. Briefly, designing reading materials based on Maimoon palace will attract students to read the story in order to increase and enhance their reading skill and vocabulary.